Performance evaluation of uncoordinated beamforming over cognitive radio network - Wan Mohd Zuferi , Wan Nadzlia Shazwanie; Ramli, Nordin; Mohamad, Hafizal; Abdullah, Khaizuran (Institute of Electrical and Electronics Engineers, Inc., 2012)
This paper presents the two strategies of jointlyoptimized uncoordinated beamforming algorithms for cognitive radio networks. Here, we evaluate the performance of signal-tointerference-plus-noise ratio (SINR) and achievable sum rate of the system when both primary and secondary users transmit concurrently over the same spectrum. We present the optimum weight design to maximize the SINR and achievable sum rate for both primary and cognitive link under the condition that the cross interference at both receivers are totally nullified. The interference cancellation is done at the secondary user and no coordination between the primary and secondary users is required as we employed uncoordinated beamforming in the networks. The fairness of the SINR performance in primary and cognitive link when the primary user employing maximal ratio combining beamformer while the secondary user employing discrete search and gradient algorithm is discussed using different number of transmit and receive antennas. Simulation results demonstrate that employing gradient algorithm at the cognitive link is optimum in terms of maximizing SINR and provides a higher rate compared to the discrete search.